Insulin-like peptide 3 (INSL3) - Anand-Ivell, Ravinder; Ivell, Richard (Elsevier, Waltham MA, 2018)
Insulin-like peptide 3 (INSL3) is a major secretory product of the steroidogenic Leydig cells of the testes in the fetus as well as in the adult. It is a constitutive product of the mature Leydig cells and hence acts as an excellent biomarker for Leydig cell functional capacity, and can be used to monitor fetal and pubertal development, as well as male ageing. Its major function is to promote the first transabdominal phase of testis descent in the fetus, interacting with RXFP2 receptors on the gubernacular ligaments. It also has functions in the adult linked to spermatogenesis, steroidogenesis and bone metabolism. INSL3 is also produced in the female as a paracrine system within the ovary serving to promote steroidogenesis within growing antral follicles.